1482: Leonardo in transito, da Firenze a Milano (Quaderni di Gargnano, 2021)
This contribution is aimed at summarizing the historical circumstances of Leonardo’s trip from Florence to Milan in 1482, by examining, in particular, their political implications and consequences. In the context of a network of personal relations – still Florentine in their origin and Medicean as for their social background – his arrival at the Sforza court seems the result of the subtle direction of Lorenzo the Magnificent, in the broader frame of the latter’s diplomatic and cultural exchanges with Ludovico the Moor, at the time of their mutual involvement in the war of Ferrara (1481-1484). Il contributo si propone di ricapitolare le circostanze storiche del “transito” di Leonardo da Firenze a Milano nel 1482, esaminandone in particolare le implicazioni e ripercussioni politiche. In una rete di relazioni ancora fiorentine e di estrazione medicea, il suo arrivo alla corte sforzesca appare il risultato della sottile regia di Lorenzo il Magnifico, nella più ampia cornice degli scambi diplomatici e culturali di quest’ultimo con Ludovico il Moro, nel frangente del loro comune coinvolgimento nella guerra di Ferrara (1481-1484).
Keywords: Leonardo da Vinci; Lorenzo il Magnifico; Ludovico il Moro; arte della guerra; vita di corte; art of war; courtly life